TRADISI NGEREBEG DALAM UPACARA AGAMA HINDU DI DESA TEGALALANG KABUPATEN GIANYAR - Ida Ayu Putu Sari; Ni Made Surawati; A.A Ketut Raka (UNHI PRESS, 2022)
Ngerebeg is an ancient tradition in the village of Pakraman Tegallalang, Gianyar, Bali. This tradition should be preserved so that the younger generation does not misunderstand what Ngerebeg really means. With this problem raised the title